Modelo de planeación de capacidades utilizando programación fraccional lineal en un contexto de múltiples criterios de decisión - Kalenatic, Dusko; López Bello, César Amilcar; González Rodríguez, Leonardo José (Ingeniería, 2005)
This paper presents a model of capacity planning for the manufacturing companies with an approach on fractional multi-criterion. This model tries to enrich decisions making process to evaluate the behavior of the productive system through relations of partial and whole productivity of the critical resources that intervene in the productive activities. The model combine linear fractional mathematical programming techniques whit goal programming techniques by the way to give original treatment proposed by the authors. The model is formulated whit the assumption of polyvalent labor force, in conformity with the current trends in the personnel training, furthermore consider the availability of the machine resource in the context of productionprocess multi-stages. With the related model its tried to give a theoretical support to different situations in which an organization can be orientating its activity for the rational utilization of its resources, besides fixing a methodology to approach the problem of management of the capacity in an environment of fractional criteria multiple. With the fractional criteria multiple model, the generated information determine the respective bottle necks, and facilitating the process of analysis, programming and planning of the productive activity, measurements and evaluation of the efficiency, and also the formulation of strategies for the improvement of the productivity and profitability of the organizations.